Photosensitive conductive paste and substrate with conductive pattern using the same
The photosensitive conductive paste with specific wavelength-absorbing dyes and conductive particles addresses microfabrication and transfer accuracy issues, enabling precise and reliable conductive pattern transfer in complex circuit boards.
Patent Information
- Application Number
- JP2023104071
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-26
- Publication Date
- 2025-01-15
AI Technical Summary
Existing methods for forming high-definition conductive patterns in complex circuit boards face challenges in microfabrication and transfer accuracy, particularly with anisotropic conductive adhesive layers, leading to difficulties in achieving precise and reliable connections.
A photosensitive conductive paste comprising a dye or pigment with a maximum absorption wavelength of 500 to 600 nm, conductive particles, an alkali-soluble resin, and a photosensitizer, which allows for precise laser transfer of conductive patterns onto substrates without the need for additional release layers, enhancing transfer accuracy and reliability.
The solution enables accurate and reliable transfer of fine conductive patterns with improved connection reliability and reduced impact from laser irradiation, allowing for precise positioning and stable electrical connections.
Smart Images

Figure 2025004403000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a photosensitive conductive paste, a substrate having a conductive pattern using the same, a method for producing the same, and a method for producing a structure having a conductive pattern. [Background technology]
[0002] In recent years, with the miniaturization of electronic components, there is a demand for a technology for forming a high-definition conductive pattern in a specific micro-area of a complicated circuit board. As such a technology, a technology for transferring a previously formed conductive pattern to a predetermined micro-area by laser irradiation has been considered. For example, a method for manufacturing a display device (see, for example, Patent Document 1) has been proposed, which includes a transfer step in which an anisotropic conductive adhesive layer provided on a substrate having transparency to laser light is placed opposite a wiring substrate, and a laser beam is irradiated from the substrate side to transfer and arrange pieces of the anisotropic conductive adhesive layer at predetermined positions on the wiring substrate, and a mounting step in which a light-emitting element is mounted on the pieces arranged at predetermined positions on the wiring substrate, and a method for manufacturing a substrate with a conductive pattern (see, for example, Patent Document 2) has been proposed, which includes a step of forming a pattern of a composition having an organic component and conductive particles on a transfer substrate, and a step of irradiating a laser from the back side of the transfer substrate to transfer the pattern to a transferee substrate. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2022 / 202934 [Patent Document 2] Patent Publication No. 2022-55760 Summary of the Invention [Problem to be solved by the invention]
[0004] However, the method described in Patent Document 1 has a problem in terms of microfabrication because it is difficult to microfabricate individual pieces of the anisotropic conductive adhesive layer. Also, the method described in Patent Document 2 allows microfabrication, but has a problem in that the transfer accuracy decreases as the pattern becomes smaller.
[0005] In view of the above problems, an object of the present invention is to provide a photosensitive conductive paste that can be finely processed and that can transfer a formed conductive pattern with high accuracy. [Means for solving the problem]
[0006] In order to solve the above problems, the present invention mainly has the following configuration. (1) A photosensitive conductive paste containing (A) a dye and / or pigment having a maximum absorption wavelength in the range of 500 to 600 nm, conductive particles (B), an alkali-soluble resin (C) and a photosensitizer (D). (2) The photosensitive conductive paste according to (1), further comprising an epoxy resin (E) having a softening point of 40°C or higher and an ICI viscosity at 150°C of 10 Pa·s or lower. (3) A photosensitive conductive paste according to (1) or (2), which when applied onto a substrate and heated at 100° C. for 10 minutes produces a dry film having a thickness of 2 μm and an OD value (λ=532 nm) of 0.5 or more. (4) The photosensitive conductive paste according to any one of (1) to (3), wherein the content of the conductive particles (B) is 10 to 30% by volume of the solid content. (5) The photosensitive conductive paste according to any one of (1) to (4), wherein the alkali-soluble resin (C) has a urethane bond. (6) The photosensitive conductive paste according to any one of (1) to (5), comprising, as the photosensitizer (D), a photopolymerization initiator (D-1) and a compound having an unsaturated double bond (D-2). (7) The photosensitive conductive paste according to (6), wherein the compound (D-2) having an unsaturated double bond has a urethane bond. (8) A substrate having a conductive pattern, the substrate having a transmittance of 50% or more of light having a wavelength of 532 nm, the conductive pattern being made of a photopolymerization product of the photosensitive conductive paste according to any one of (1) to (7). (9) The substrate with a conductive pattern according to (8), wherein the conductive pattern has a height of 0.5 to 3 μm. (10) A method for producing a substrate having a conductive pattern according to (8), comprising the steps of forming a film made of the photosensitive conductive paste according to any one of (1) to (7) on a substrate that transmits 50% or more of light having a wavelength of 532 nm, exposing the film to light, and developing the film to form a conductive pattern (a conductive pattern forming step). (11) A method for producing a structure with a conductive pattern, comprising a step of irradiating a laser beam having a wavelength of 500 to 600 nm from the substrate side of the substrate with a conductive pattern according to (8) or (9) that transmits light with a wavelength of 532 nm, thereby transferring the conductive pattern to an electrode portion of the substrate with an electrode or an electronic component, or to a wiring break portion of the substrate with an electrode or an electronic component (conductive pattern transfer step). Effect of the Invention
[0007] According to the photosensitive conductive paste of the present invention, a fine conductive pattern can be transferred with high precision. [Brief description of the drawings]
[0008] [Figure 1] 1 is a schematic diagram showing an example of a method for producing a structure with a conductive pattern of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a structure with a conductive pattern obtained in an example. [Diagram 3] FIG. 2 is a schematic cross-sectional view of a sample for evaluating connectivity used in the examples. [Figure 4] FIG. 2 is a schematic diagram of a sample for evaluating electrical conductivity used in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The photosensitive conductive paste of the present invention contains a dye and / or pigment (A) having a maximum absorption wavelength in the range of 500 to 600 nm (hereinafter, sometimes abbreviated as "dye / pigment (A)"), conductive particles (B), an alkali-soluble resin (C), and a photosensitizer (D). The dye / pigment (A) has a function of efficiently absorbing laser light and converting it into thermal energy in a conductive pattern transfer step to improve transfer accuracy when a substrate with a conductive pattern, which will be described later, obtained using the photosensitive conductive paste of the present invention, is applied to a method for producing a structure with a conductive pattern, which will be described later. The conductive particles (B) have a function of imparting conductivity to the conductive pattern in the substrate with a conductive pattern, which will be described later, obtained using the photosensitive conductive paste of the present invention. The alkali-soluble resin (C) and the photosensitizer (D) have a function of imparting photosensitivity to the conductive paste, enabling fine processing by photolithography. In addition, since the exposure wavelength in general photolithography is shorter than 500 to 600 nm, by selecting a dye / pigment (A) that has a maximum absorption wavelength in the range of 500 to 600 nm, it is possible to improve the transfer accuracy while maintaining the exposure sensitivity and fine processability in photolithography.
[0010] As the dye / pigment (A), for example, FDG-001 (λmax=503nm), FDG-002 (λmax=525nm), FDG-003 (λmax=547nm), FDG-00 manufactured by Yamada Chemical Industry Co., Ltd. 4 (λmax=576nm), FDG-005 (λmax=583nm), FDG-006 (λmax=585nm), FDG-007 (λmax=594nm), Chugai manufactured by Taiyo Fine Chemical Co., Ltd. Amino Fast Pink RH / C(λmax=536nm), PinkBase(λmax=526nm), “Chuganol(R)” Anthracene Red G(λmax=521nm), Acid Red106(λmax=542nm), Acid Red151(λmax=510nm), “Chugacid(R)” Red Examples of such a material include FCH (λmax=505 nm), VALIFAST (registered trademark) RED1308 (λmax=536 nm) manufactured by Orient Chemical Industry Co., Ltd., and FS Scarlet 1307 (λmax=520 nm) manufactured by Arimoto Chemical Industry Co., Ltd. Two or more of these may be contained. Among these, those having a maximum absorption wavelength in the range of 520 to 550 nm are preferred, and can further improve the process margin and transfer accuracy of laser transfer in the conductive pattern transfer step described below.
[0011] The content of the dye / pigment (A) in the photosensitive conductive paste of the present invention is preferably 0.01 to 5 parts by weight per 100 parts by weight of the solid content excluding the conductive particles (B). When the content of the dye / pigment (A) is 0.01 parts by weight or more, the exposure sensitivity and laser transfer performance in photolithography can be improved due to the sensitizing effect on the photosensitizer (D). The content of the dye / pigment (A) is more preferably 0.05 parts by weight or more, even more preferably 0.1 parts by weight or more, and even more preferably 0.3 parts by weight or more. On the other hand, when the content of the dye / pigment (A) is 5 parts by weight or less, damage to the pattern during laser transfer can be suppressed, and the die shear strength and connection reliability of the structure with a conductive pattern can be improved.
[0012] Examples of the conductive particles (B) include particles containing metals such as silver, gold, copper, platinum, lead, tin, nickel, aluminum, tungsten, molybdenum, chromium, titanium, and indium, alloys thereof, ITO, tin oxide, antimony-doped tin oxide, and carbon black. Examples also include insulating particles such as resins and inorganic oxides, and conductive particles having a coating layer of the above-mentioned metals or carbon on the surface. Two or more of these may be contained. Among these, carbon black and silver particles having a carbon coating layer are preferred because they have an absorption range at the laser wavelength, efficiently convert the energy during laser irradiation in the conductive pattern transfer process described below into heat to easily decompose the organic components of the conductive pattern, and have excellent laser transferability. Furthermore, carbon black can stably connect electrically to molybdenum and ITO, which are considered to be difficult to connect electrically.
[0013] The aspect ratio, which is the value obtained by dividing the major axis length of the conductive particles (B) by the minor axis length, is preferably 1.0 or more from the viewpoint of increasing the contact probability between the conductive particles (B). On the other hand, the aspect ratio of the conductive particles is preferably 3.0 or less, more preferably 2.0 or less, from the viewpoint of suppressing the shielding of the exposure light in the exposure process and widening the development margin in the conductive pattern formation process described later. Here, the aspect ratio of the conductive particles (B) can be obtained by observing the conductive particles (B) at a magnification of 15,000 times using a scanning electron microscope (SEM) or a transmission electron microscope (TEM), measuring the major axis length and minor axis length of each of 100 randomly selected primary particles of the conductive particles (B), and calculating the number average of the aspect ratio obtained from the average of both values.
[0014] From the viewpoint of dispersibility, the particle diameter of the conductive particles (B) is preferably 0.01 μm or more. On the other hand, from the viewpoint of further improving the surface smoothness and dimensional accuracy of the conductive pattern, and the transfer accuracy in the conductive pattern transfer step described later, the particle diameter of the conductive particles (B) is preferably 1.0 μm or less, more preferably 0.2 μm or less. Here, the particle diameter of the conductive particles (B) can be determined by a dynamic light scattering method. Specifically, the particle diameter can be determined by irradiating a dispersion liquid having a conductive particle (B) concentration of 5 to 30% by volume with light having a wavelength of 780 nm using a semiconductor laser, measuring the scattered light, and then performing frequency analysis using the FFT-heterodyne method.
[0015] The content of the conductive particles (B) in the photosensitive conductive paste of the present invention is preferably 10% by volume or more, more preferably 15% by volume or more, based on the solid content of the photosensitive conductive paste from the viewpoint of improving the conductivity. On the other hand, the content of the conductive particles is preferably 30% by volume or less, more preferably 25% by volume or less, from the viewpoints of improving the transfer accuracy in the pattern transfer step by appropriately containing an organic component, of further reducing the impact in the pattern transfer step and further improving the connection reliability, and of improving the die shear strength between the electronic component and the patterned structure. Here, the content of the conductive particles (B) in the solid content of the photosensitive conductive paste can be calculated by applying the photosensitive conductive paste onto a substrate, drying and removing any liquid components such as a solvent from the photosensitive conductive composition layer, scraping off a portion of the paste, and using a thermogravimetric analyzer to hold the paste in air at 600°C for 1 hour to remove the organic components. From the remaining weight ratio (thermogravimetric residual ratio) and the reduced weight ratio (thermogravimetric reduction ratio), the weight fraction of the conductive particles (B) and the weight fraction of the organic components are calculated, respectively, using the following formula [1]. Here, the density of the organic components is 1.1 g / cm 3 However, if the composition ratio of the raw materials of the photosensitive conductive paste is known, it can be calculated from that composition ratio.
[0016]
number
[0017] Examples of the alkali-soluble resin (C) include carboxyl group-containing acrylic copolymers, carboxylic acid-modified epoxy resins, carboxylic acid-modified phenolic resins, polyamic acids, carboxylic acid-modified polysiloxanes, and phenolic resins. Two or more of these may be included. Among these, carboxyl group-containing acrylic copolymers and carboxylic acid-modified epoxy resins are preferred because of their high ultraviolet light transmittance. As the carboxyl group-containing acrylic copolymer, a copolymer of an acrylic monomer and an unsaturated acid or its acid anhydride is preferred.
[0018] Examples of acrylic monomers include acrylic acid, methyl acrylate, ethyl acrylate, 2-ethylhexyl acrylate, n-butyl acrylate, iso-butyl acrylate, iso-propane acrylate, glycidyl acrylate, butoxytriethylene glycol acrylate, dicyclopentanyl acrylate, dicyclopentenyl acrylate, 2-hydroxyethyl acrylate, isobornyl acrylate, 2-hydroxypropyl acrylate, isodexyl acrylate, isooctyl acrylate, lauryl acrylate, and 2-methoxyethyl acrylate. Acrylate, methoxyethylene glycol acrylate, methoxydiethylene glycol acrylate, octafluoropentyl acrylate, phenoxyethyl acrylate, stearyl acrylate, trifluoroethyl acrylate, aminoethyl acrylate, phenyl acrylate, phenoxyethyl acrylate, 1-naphthyl acrylate, 2-naphthyl acrylate, thiophenol acrylate, benzyl mercaptan acrylate, allylated cyclohexyl diacrylate, methoxylated cyclohexyl diacrylate, 1,4-butanediol diacrylate, 1,3-butylene glycol diacrylate, ethylene glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, polyethylene glycol diacrylate, neopentyl glycol diacrylate, propylene glycol diacrylate, polypropylene glycol diacrylate, triglycerol diacrylate, trimethylolpropane triacrylate, ditrimethylolpropane tetraacrylate, dipentaerythritol monohydroxypentaacrylate, dipentaerythritol hexaacrylate, acrylamide, N-methoxymethylacrylamide, N-ethoxymethylacrylamide, Nn-butoxymethylacrylamide, N-isobutoxymethylacrylamide, methacrylphenol, methacrylamide phenol, acrylic acid adduct of ethylene glycol diglycidyl ether having a hydroxyl group in which the epoxy group is ring-opened with an unsaturated acid, acrylic acid adduct of diethylene glycol diglycidyl ether ... Examples of the monomer include epoxy acrylate monomers such as acrylic acid adduct of ethyl glycol diglycidyl ether, acrylic acid adduct of glycerin diglycidyl ether, acrylic acid adduct of bisphenol A diglycidyl ether, acrylic acid adduct of bisphenol F, and acrylic acid adduct of cresol novolac; phenolic hydroxyl group-containing monomers such as γ-acryloxypropyltrimethoxysilane, N-(2-hydroxyphenyl)acrylamide, N-(3-hydroxyphenyl)acrylamide, N-(4-hydroxyphenyl)acrylamide, o-hydroxyphenyl acrylate, m-hydroxyphenyl acrylate, p-hydroxyphenyl acrylate, o-hydroxystyrene, m-hydroxystyrene, p-hydroxystyrene, 2-(2-hydroxyphenyl)ethyl acrylate, 2-(3-hydroxyphenyl)ethyl acrylate, and 2-(4-hydroxyphenyl)ethyl acrylate; and compounds in which the acryloyl group of these monomers is replaced with a methacryloyl group. Two or more of these may be used.
[0019] Examples of the unsaturated acid or its anhydride include acrylic acid, methacrylic acid, itaconic acid, crotonic acid, maleic acid, fumaric acid, vinyl acetate, and their anhydrides. Two or more of these may be used. The acid value of the carboxyl group-containing acrylic copolymer can be adjusted by the copolymerization ratio of the unsaturated acid.
[0020] The carboxylic acid-modified epoxy resin is preferably a reaction product of an epoxy compound and a carboxyl compound having an unsaturated double bond. The carboxylic acid-modified epoxy resin is a resin in which an epoxy group is modified with a carboxylic acid, and does not contain an epoxy group.
[0021] Examples of epoxy compounds include glycidyl ethers, glycidyl amines, and epoxy resins. More specifically, examples of glycidyl ethers include methyl glycidyl ether, ethyl glycidyl ether, butyl glycidyl ether, ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, bisphenol A diglycidyl ether, hydrogenated bisphenol A diglycidyl ether, bisphenol F diglycidyl ether, bisphenol S diglycidyl ether, bisphenol fluorene diglycidyl ether, biphenol diglycidyl ether, tetramethyl biphenol glycidyl ether, trimethylolpropane triglycidyl ether, and 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate. Examples of glycidyl amines include tert-butyl glycidyl amine. Examples of epoxy resins include bisphenol A type epoxy resins, bisphenol F type epoxy resins, biphenyl type epoxy resins, novolac type epoxy resins, hydrogenated bisphenol A type epoxy resins, etc. Two or more of these may be used.
[0022] An unsaturated double bond can be introduced by reacting a compound having an unsaturated double bond, such as glycidyl (meth)acrylate, with the above-mentioned carboxyl group-containing acrylic copolymer or carboxylic acid-modified epoxy resin. By introducing an unsaturated double bond into the alkali-soluble resin (C), the crosslink density of the exposed area can be improved and the development margin can be widened in the conductive pattern forming process described below.
[0023] The alkali-soluble resin (C) preferably has a urethane bond. When the alkali-soluble resin (C) has a urethane bond, it is possible to reduce the impact in the conductive pattern transfer step described below and to suppress damage to the conductive pattern.
[0024] The acid value of the alkali-soluble resin (C) is preferably 50 to 250 mgKOH / g. If the acid value of the alkali-soluble resin (C) is 50 mgKOH / g or more, it has excellent solubility in a developer, and the generation of development residues can be suppressed in the conductive pattern forming process described below. The acid value of the alkali-soluble resin (C) is more preferably 60 mgKOH / g or more. On the other hand, if the acid value of the alkali-soluble resin (C) is 250 mgKOH / g or less, excessive dissolution in a developer can be suppressed, and the film loss of the conductive pattern can be suppressed. The acid value of the alkali-soluble resin (C) is more preferably 200 mgKOH / g or less. The acid value of the alkali-soluble resin (C) can be measured in accordance with JIS K 0070 (1992).
[0025] The acid value of the alkali-soluble resin (C) can be adjusted to a desired range by adjusting the ratio of unsaturated acid in the constituent components, for example, in the case of a carboxyl group-containing acrylic copolymer. In the case of a carboxylic acid-modified epoxy resin, it can be adjusted to a desired range by reacting with a polybasic acid anhydride. In the case of a carboxylic acid-modified phenolic resin, it can be adjusted to a desired range by adjusting the ratio of polybasic acid anhydride in the constituent components.
[0026] The content of the alkali-soluble resin (C) in the photosensitive conductive paste of the present invention is preferably 15 to 40 parts by weight per 100 parts by weight of the solid content excluding the conductive particles (B). When the content of the alkali-soluble resin (C) is 15 parts by weight or more, peeling development phenomenon during development can be suppressed in the conductive pattern forming step described below, and a finer conductive pattern can be formed. On the other hand, when the content of the alkali-soluble resin (C) is 40 parts by weight or less, pattern flow due to development can be suppressed in the conductive pattern forming step, and a finer conductive pattern can be formed.
[0027] Examples of the photosensitizer (D) include, for example, a photopolymerization initiator (D-1) and a compound (D-2) having an unsaturated double bond when the photosensitive conductive paste is to have negative photosensitivity, while examples of the photosensitizer (D) include a photoacid generator (D-3) when the photosensitive conductive paste is to have positive photosensitivity.
[0028] Examples of the photopolymerization initiator (D-1) include benzophenone derivatives, acetophenone derivatives, thioxanthone derivatives, benzyl derivatives, benzoin derivatives, oxime compounds, α-hydroxyketone compounds, α-aminoalkylphenone compounds, phosphine oxide compounds, anthrone compounds, anthraquinone compounds, etc. Two or more of these may be contained.
[0029] The compound (D-2) having an unsaturated double bond is preferably a monomer or oligomer having an acryloyl group or a methacryloyl group. Examples of compounds having two of these groups in the molecule include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, glycerin di(meth)acrylate, 2-hydroxy-3-acryloyloxypropyl (meth)acrylate, dimethylol-tricyclodecane di(meth)acrylate, tripropylene glycol di(meth)arylate, dioxane glycol di(meth)arylate, cyclohexanedimethanol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, ethoxylated (4) bisphenol A di(meth)acrylate, ethoxylated (10) bisphenol A di(meth)acrylate, (meth)acrylic acid adduct of ethylene glycol diglycidyl ether, and (meth)acrylic acid adduct of neopentyl glycol diglycidyl ether. Examples of compounds having three acryloyl groups or methacryloyl groups in the molecule include pentaerythritol tri(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolpropane ethoxy tri(meth)acrylate, and glycerin propoxy tri(meth)acrylate. Examples of compounds having four or more acryloyl groups or methacryloyl groups in the molecule include dipentaerythritol hexa(meth)acrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol ethoxy tetra(meth)acrylate, and ditrimethylolpropane tetra(meth)acrylate. Two or more of these may be contained. Note that (meth)acrylate means acrylate or methacrylate.
[0030] The compound (D-2) having an unsaturated double bond preferably has a urethane bond. By having the compound (D-2) having an unsaturated double bond have a urethane bond, it is possible to reduce the impact in the conductive pattern transfer step described later and suppress damage to the conductive pattern. Examples of the compound (D-2) having an unsaturated double bond having a urethane bond include urethane acrylates "EBECRYL (registered trademark)" 204, "EBECRYL" 210, "EBECRYL" 220, "EBECRYL" 264, "EBECRYL" 265, and "EBECRYL" 284 manufactured by Daicel-Cytec Co., Ltd., urethane acrylates CN972, CN975, and CN978 manufactured by Sartomer Co., Ltd., and urethane acrylates "KAYARAD (registered trademark)" UX-3204, "KAYARAD" UX-4101, "KAYARAD" UXF-4002, and "KAYARAD" UX-5000 manufactured by Nippon Kayaku Co., Ltd.
[0031] Examples of the photoacid generator (D-3) include diazodisulfone compounds, triphenylsulfonium compounds, and quinonediazide compounds. Two or more of these may be included. Examples of the diazodisulfone compounds include bis(cyclohexylsulfonyl)diazomethane, bis(t-butylsulfonyl)diazomethane, and bis(4-methylphenylsulfonyl)diazomethane. Examples of the triphenylsulfonium compounds include diphenyl-4-methylphenylsulfonium trifluoromethanesulfonate, diphenyl-2,4,6-trimethylphenylsulfonium p-toluenesulfonate, and diphenyl(4-methoxyphenyl)sulfonium trifluoromethanesulfonate. Examples of the quinone diazide compound include a polyhydroxy compound to which a sulfonic acid of quinone diazide is bonded via ester, a polyamino compound to which a sulfonic acid of quinone diazide is bonded via sulfonamide, and a polyhydroxy polyamino compound to which a sulfonic acid of quinone diazide is bonded via ester and / or sulfonamide. All functional groups of these polyhydroxy compounds and polyamino compounds do not have to be substituted with quinone diazide, but it is preferable that 50 mol% or more of the total functional groups are substituted with quinone diazide. The quinone diazide compound may be either a 5-naphthoquinone diazide sulfonyl group or a 4-naphthoquinone diazide sulfonyl group. A compound having both of these groups in the same molecule may be used, or compounds using different groups may be used in combination.
[0032] The content of the photosensitizer (D) in the photosensitive conductive paste of the present invention is preferably 0.05 to 80 parts by weight based on 100 parts by weight of the solid content excluding the conductive particles (B). When the photosensitizer (D) contains a photopolymerization initiator (D-1) and a compound (D-2) having an unsaturated double bond, the total content thereof is preferably 5 parts by weight or more, and in the conductive pattern forming process described below, the hardening density of the exposed part is increased, and a finer conductive pattern can be formed. On the other hand, the total content of the photopolymerization initiator (D-1) and the compound (D-2) having an unsaturated double bond is preferably 80 parts by weight or less, which can suppress side edges due to excessive light absorption in the conductive pattern forming process, form a finer conductive pattern, and further improve the transfer accuracy in the conductive pattern transfer process. In addition, when the photosensitizer (D) contains a photoacid generator (D-3), the content thereof is preferably 0.05 parts by weight or more, and in the conductive pattern forming process, the solubility of the exposed part in the developer is improved, and therefore, the rattling of the pattern edge due to peeling development can be suppressed. On the other hand, the content of the photoacid generator (D-3) is preferably 30 parts by mass or less, which can suppress excessive light absorption by the photoacid generator (D-3) and suppress the generation of residues in the conductive pattern formation step.
[0033] The photosensitive conductive paste of the present invention preferably further contains an epoxy resin, which can improve the mountability of electronic components, the adhesion between the conductive pattern and the electrode-attached substrate or electronic components, and can improve the die shear strength and connection reliability in a structure with a conductive pattern described later. Among the epoxy resins, an epoxy resin (E) (hereinafter sometimes abbreviated as "epoxy resin (E)") having a softening point of 40°C or higher and an ICI viscosity at 150°C of 10 Pa·s or lower is preferable. When the softening point is 40°C or higher, excessive bump crushing during mounting can be suppressed, and short circuit defects can be suppressed, and when the ICI viscosity at 150°C is 10 Pa·s or lower, the mountability of electronic components can be improved, and further, when the structure with a conductive pattern described later is formed, the die shear strength and connection reliability can be improved. The ICI viscosity at 150°C is more preferably 1 Pa·s or lower.
[0034] Examples of the epoxy resin (E) include CER-3000-L, NC-3000, NC-3000H, NC-3100, NC-2000-L, XD-1000, NC-7000L, NC-7300L, EPPN-501H, EPPN-501HY, EPPN-502H, EOCN-1020, EOCN-102S, EOCN-103S, EOCN-104S, CER-1020, EPPN-201, and N manufactured by Nippon Kayaku Co., Ltd. -660, N-665, N-670, N-673, N-680, N-695, N-655-EXP-S, N-662-EXP-S, N-670-EXP-S, N-685-EXP-S, N-740, N-770, N-775, N-865, N-885, N-890, HP-7200L, HP-7200, HP-7200H, HP-7200HHH, HP-4700, HP-4710, HP-4770, HP-5000, etc. These may be contained in two or more kinds. Among these, except for N-680, N-695, HP-7200H, and HP-7200HHH, the ICI viscosity at 150 ° C. is 1 Pa s or less, and it is preferable.
[0035] The content of the epoxy resin (E) in the photosensitive conductive paste of the present invention is preferably 1 to 30 parts by weight based on 100 parts by weight of the solid content excluding the conductive particles (B). When the content of the epoxy resin (E) is 1 part by weight or more, in a structure with a conductive pattern described below, the mountability of electronic components and the adhesion between the conductive pattern and the electrode-attached substrate or electronic components can be improved, and the die shear strength and connection reliability can be improved. On the other hand, when the content of the epoxy resin (E) is 30 parts by weight or less, in the conductive pattern forming step described below, the photocuring reaction during exposure proceeds smoothly and the crosslink density increases, so that a finer conductive pattern can be formed.
[0036] The photosensitive conductive paste of the present invention preferably further contains a solvent. Examples of the solvent include N,N-dimethylacetamide, N,N-dimethylformamide, N-methyl-2-pyrrolidone, dimethylimidazolidinone, dimethylsulfoxide, γ-butyrolactone, ethyl lactate, 1-methoxy-2-propanol, 1-ethoxy-2-propanol, ethylene glycol mono-n-propyl ether, diacetone alcohol, tetrahydrofurfuryl alcohol, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether, diethylene glycol, and 2,2,4,-trimethyl-1,3-pentanediol monoisobutyrate. Two or more of these may be contained. Among these, a solvent having a boiling point of 120° C. or more is preferable, and the film thickness variation can be suppressed in the conductive pattern forming process described later.
[0037] The photosensitive conductive paste of the present invention may contain additives such as a plasticizer, a leveling agent, a surfactant, a silane coupling agent, an antifoaming agent, and a pigment, to the extent that the desired properties are not impaired.
[0038] The photosensitive conductive paste of the present invention can be obtained, for example, by mixing the above-mentioned dye / pigment (A), conductive particles (B), alkali-soluble resin (C), photosensitizer (D), and, if necessary, epoxy resin (E), solvent and other additives. Examples of the mixing device include a dispersing machine or kneading machine such as a three-roller mill, a ball mill, a planetary ball mill, or a bead mill.
[0039] When the photosensitive conductive paste of the present invention is applied onto a substrate and heated at 100°C for 10 minutes to form a dry film with a thickness of 2 μm, the OD value of the dry film at a wavelength of 532 nm is preferably 0.5 or more, which can further improve the transfer accuracy in the conductive pattern transfer step described below. Here, the OD value of the dry film can be determined by measuring the transmitted light intensity at a wavelength of 532 nm using a microspectrometer for five randomly selected points on the dry film, determining each OD value from the following relational formula (1), and calculating the average. OD value = log10(I0 / I) (1) Here, I0 is the incident light intensity, and I is the transmitted light intensity. The OD value of the dry film at a wavelength of 532 nm can be adjusted to a desired range, for example, by the type and content of the dye / pigment (A).
[0040] The photosensitive conductive paste of the present invention is applied onto a substrate, and the dried film is exposed to light in a desired pattern as required, and developed to form a fine pattern on the substrate. The photosensitive conductive paste of the present invention can be suitably used, for example, as a wiring for repairing a wiring defect or as a bump material for electrically connecting an electrode on a substrate to an electrode of an electronic component.
[0041] Next, the substrate with a conductive pattern of the present invention will be described. The substrate with a conductive pattern of the present invention has a conductive pattern made of a photopolymerization product of the photosensitive conductive paste on a substrate that transmits 50% or more of light with a wavelength of 532 nm. The conductive pattern can be transferred to a desired location by irradiating the substrate side of the substrate with such a conductive pattern with laser light having a wavelength of 500 to 600 nm. The substrate with a conductive pattern of the present invention contains the dye / pigment (A) described above in the conductive pattern, and therefore can be transferred to a desired location with high accuracy by laser irradiation without requiring a release layer, sacrificial layer, or release layer.
[0042] Examples of substrates that transmit 50% or more of light with a wavelength of 532 nm include glass substrates, quartz substrates, sapphire substrates, etc. Among these, glass substrates are preferable.
[0043] The height of the conductive pattern is preferably 0.5 μm or more from the viewpoint of suppressing microcracks in the conductive pattern transfer process described later and improving connection reliability. On the other hand, the height of the conductive pattern is preferably 3 μm or less from the viewpoint of further improving the transfer accuracy, suppressing the spread of the pattern when an electronic component is mounted, and suppressing short circuits with surrounding electrodes. Here, the height of the conductive pattern refers to the average value of the heights of 10 randomly selected conductive patterns calculated assuming that the pattern shape is rectangular. More specifically, for 10 patterns randomly selected from the conductive pattern-attached substrate, a laser microscope VK-X250 manufactured by Keyence Corporation is used to perform laser scanning on the surface at a magnification of 500 to 1,000 times to measure the shape of the surface. The height of the conductive pattern can be obtained by calculating the pattern height assuming that the pattern shape is rectangular using an analysis mode attached to the device, and calculating the average value.
[0044] The aspect ratio of the conductive pattern is preferably 0.1 or more from the viewpoint of suppressing the occurrence of microcracks in the conductive pattern transfer process described later and improving the connection reliability. On the other hand, the aspect ratio of the conductive pattern is preferably 0.4 or less from the viewpoint of increasing the directivity in the conductive pattern transfer process and improving the transfer accuracy. Here, the aspect ratio of the conductive pattern refers to the average value of the values obtained by dividing the height of the conductive pattern by the diameter of the conductive pattern for 10 randomly selected conductive patterns. If the conductive pattern is cylindrical, the diameter is the conductive pattern diameter, and if the conductive pattern is not cylindrical, the diameter when converted into a cylinder with the same contact area is the conductive pattern diameter.
[0045] The contact area between the conductive pattern and the substrate is set to 16 μm in order to further improve positional accuracy. 2 On the other hand, the contact area between the conductive pattern and the substrate is preferably 500 μm or more from the viewpoint of uniformly generating ablation at the contact interface during laser irradiation and further improving transfer accuracy. 2The following is preferable. Here, the contact area between the conductive pattern and the substrate refers to the average value of the contact area between 10 randomly selected conductive patterns and the substrate. More specifically, the images obtained by observing 10 randomly selected conductive patterns with an optical microscope at a magnification of 500 to 1,000 times are binarized using image analysis and measurement software based on the brightness of the measurement image, and the area of the dark area, which is the contact area between the substrate and the conductive pattern, is calculated, and the average value is calculated. The contact area can be adjusted to a desired range by adjusting the dimensions of the photomask, etc.
[0046] The method for producing a substrate with a conductive pattern of the present invention preferably includes a step of forming a film made of the photosensitive conductive paste of the present invention on a substrate that transmits 50% or more of light with a wavelength of 532 nm as described above, and then exposing and developing the film to form a conductive pattern (conductive pattern formation step).
[0047] Examples of methods for forming a film made of a photosensitive conductive paste on a substrate that transmits 50% or more of light with a wavelength of 532 nm include printing methods such as screen printing, and coater application such as spin coating and a slit die coater.
[0048] When the photosensitive conductive paste contains a solvent, it is preferable to remove the solvent by drying.
[0049] The OD value of a film made of a photosensitive conductive paste (or a dried film if the photosensitive conductive paste contains a solvent) at a wavelength of 532 nm is preferably 0.5 or more, which can further improve the transfer accuracy in the conductive pattern transfer process described below.
[0050] Next, the obtained film is exposed to a desired pattern. Examples of the exposure light source include a mercury lamp or an LED's i-line (365 nm) or h-line (405 nm). Examples of the exposure method include contact exposure, proximity exposure, reduced projection exposure, and direct writing exposure.
[0051] Next, the uncured portion is removed by development to form a pattern. Examples of the developer include alkaline developers such as aqueous solutions of tetramethylammonium hydroxide, diethanolamine, diethylaminoethanol, sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, triethylamine, diethylamine, methylamine, dimethylamine, dimethylaminoethyl acetate, dimethylaminoethanol, dimethylaminoethyl methacrylate, cyclohexylamine, ethylenediamine, and hexamethylenediamine. Examples of the development method include shower development, paddle development, and dip development.
[0052] The pattern shape may be, for example, a rectangular, circular, elliptical, triangular, polygonal, or a combination of these in plan view.
[0053] Next, a method for producing a structure with a conductive pattern using the substrate with a conductive pattern of the present invention will be described. The structure with a conductive pattern in the present invention refers to a substrate with an electrode or an electrode part of an electronic component, or a structure having a conductive pattern in a wiring break part of an electrode part of an electronic component. The method for producing a structure with a conductive pattern of the present invention includes a step of irradiating a laser light with a wavelength of 500 to 600 nm from the substrate side that transmits light with a wavelength of 532 nm of the substrate with the conductive pattern described above, thereby transferring the conductive pattern to the electrode part of the substrate with an electrode or the wiring break part of the electronic component (conductive pattern transfer step).
[0054] 1 shows a schematic diagram of an example of a method for manufacturing a structure with a conductive pattern of the present invention using the above-mentioned substrate with a conductive pattern. In (a), a substrate with a conductive pattern is prepared in which a conductive pattern 1 is formed on a soda glass substrate 2. In (b), a laser 3 is irradiated from the soda glass substrate 2 side of the substrate with a conductive pattern, and the conductive pattern 1 is transferred to a transfer substrate 4. Examples of the transfer substrate 4 include a substrate with an electrode and an electronic component.
[0055] In the conductive pattern transfer process, the conductive pattern is heated by laser light that passes through a substrate that is transparent to light with a wavelength of 532 nm. This decomposes organic components in the conductive pattern near the interface with the substrate, such as the dye / pigment (A), alkali-soluble resin (C), and photosensitizer (D), causing the conductive pattern to peel off from the substrate and be transferred to the electrode parts of the electrode-attached substrate or to the broken wiring parts of the electronic components.
[0056] In the present invention, the conductive pattern contains the dye / pigment (A), and thus can efficiently absorb laser light and convert it into thermal energy, and can be transferred to a desired position with high accuracy without the need for a release layer, sacrificial layer, release layer, etc. Since the transferability is excellent even when the laser irradiation intensity is low, decomposition of organic matter and impact of the conductive pattern due to laser irradiation can be suppressed, and connection reliability can be improved.
[0057] Examples of the laser to be irradiated include solid-state lasers with wavelengths of 355 nm and 532 nm. In view of the relationship with the exposure wavelength in the conductive pattern forming process described above, a solid-state laser with a wavelength of 532 nm is preferred. The output of the laser is 50 to 600 mJ / cm. 2 The laser output is preferably 50 mJ / cm 2 If the laser output is 600 mJ / cm or more, the conductive pattern is less susceptible to variations in adhesion between the conductive pattern and the substrate, and the transfer accuracy can be further improved. 2 If the laser output is less than 500 mJ / cm, the impact can be more mitigated and the connection reliability can be improved. 2 The following is more preferred:
[0058] Examples of the substrate with electrodes include TFT substrates and printed wiring boards having electrodes and wiring containing molybdenum, titanium, ITO, Cu, Ag, Ag, etc. Examples of electronic components include LED chips having gold electrodes and gold wiring, and inductors and capacitors having copper electrodes and copper wiring. Among these, those having electrodes and wiring containing molybdenum, titanium, and ITO are preferred because they cause less ion migration and the generation of intermetallic compounds. Electrodes and wiring containing these are preferably used when carbon black particles are used as the conductive particles (B) because they have high connection reliability with carbon black. EXAMPLES
[0059] The present invention will be described below with reference to examples, but the present invention is not limited to these examples.
[0060] The evaluation methods in each example are as follows.
[0061] <Exposure sensitivity> The photosensitive conductive paste obtained in each of the Examples and Comparative Examples was applied onto a glass substrate and dried in an oven at 100° C. for 10 minutes to form a dry film with a thickness of 2 μm. An exposure machine equipped with an ultra-high pressure mercury lamp was used to set the exposure dose to 300 mJ / cm. 2 to 1,200 mJ / cm 2 Up to 100mJ / cm 2 While changing the exposure time in increments, 100 circular patterns with a diameter of 10 μm were exposed and developed using an alkaline developer. The developed patterns were magnified and observed using a microscope, and the minimum exposure amount at which no pattern peeling was observed was defined as the exposure sensitivity.
[0062] <OD value of dry film> The photosensitive conductive paste obtained in each Example and Comparative Example was applied onto a soda glass substrate using a spin coater, and dried in a drying oven at 100° C. for 10 minutes to form a dry film with a thickness of 2 μm. Five randomly selected points on the dry film were measured for the transmitted light intensity at a wavelength of 532 nm using a microspectrometer (MSV-5500 manufactured by JASCO Corporation), and the OD value of each was calculated, and the average value was calculated.
[0063] <Contact area between conductive pattern and substrate> In each example and comparative example, after forming a conductive pattern on a substrate, 10 randomly selected conductive patterns were photographed at a magnification of 500 to 1,000 times using a microscope VHX-5500 manufactured by Keyence Corporation, and the images were binarized using the brightness of the measurement images as a reference in the image analysis mode. For the binarized images, the area of the dark areas, which were the contact areas between each conductive pattern and the substrate, was calculated, and the average value was calculated to determine the contact area between each conductive pattern and the substrate.
[0064] <Transfer accuracy> For 10 conductive patterns randomly selected from the glass substrates with conductive patterns obtained in each Example and Comparative Example, the conductive patterns were observed using an optical microscope from the side opposite to the side on which the conductive pattern was formed, and the amount of deviation between the center of the pattern and the intersection of the cross marks on the transferred object was measured and the average value was calculated.
[0065] <Conductivity> Three conductive patterns were randomly selected from the glass substrates with conductive patterns obtained in each Example and Comparative Example, and a laser with a wavelength of 532 nm was applied at 300 mJ / cm from the back side of the glass substrate. 2 The conductive pattern structure was heated at a temperature of 200° C. for 20 minutes using an oven after irradiating the conductive material and landing the droplets between the disconnected portions (disconnection width: 5 μm) of the Au wiring 9 of the conductivity evaluation sample shown in FIG. 4. Thereafter, points c and d of the conductive pattern structure were connected with a tester, and those that were conductive were marked with an ◯, and those that were not conductive were marked with an ×.
[0066] <Connectivity> A 3 mm square silicon chip having electrodes was thermocompressed onto the conductive patterned structures obtained in each of the Examples and Comparative Examples at a temperature of 120°C and a pressure of 1 MPa for 5 seconds, and then heated at a temperature of 200°C for 20 minutes using an oven. This resulted in a sample for connectivity evaluation shown in FIG. 3. The sample for connectivity evaluation was a silicon chip mounting board in which an electrode 8 of a silicon chip 7 was bonded onto an electrode 6 of a printed wiring board 5 via a conductive pattern 1. The resistance between points a and b of the electrode 6 was then measured using a tester.
[0067] <Connection reliability> The silicon chip mounting boards produced in the above-mentioned <connectivity> evaluation were subjected to 500 cycles of standing in environments at -55°C and 125°C for one hour each, and then the resistance was measured in the same manner as in the above-mentioned <connectivity> evaluation. The change in resistance before and after heating and cooling was calculated using the following formula to evaluate the connection reliability. The closer the resistance change is to 1, the higher the connection reliability. Resistance change = resistance after heating / cooling / resistance before heating / cooling.
[0068] <Die shear strength> The die shear strength of the silicon chip mounting substrates produced in the above-mentioned <connectivity> evaluation was measured using a die shear strength measuring device (Dage Series 4000; manufactured by Dage) at a temperature of 25° C. and a shear rate of 200 μm / sec.
[0069] The materials used in the examples and comparative examples are as follows. [Dye / pigment (A) with maximum absorption wavelength in the range of 500 to 600 nm] ·FDG-001: Manufactured by Yamada Chemical Industry Co., Ltd. (λmax=503nm) ·FDG-002: Manufactured by Yamada Chemical Co., Ltd. (λmax=525nm) ·FDG-004: Manufactured by Yamada Chemical Industry Co., Ltd. (λmax=576nm) [Conductive particles (B)] Ag particles: Ag particles manufactured by DOWA Electronics Co., Ltd. (average particle diameter 300 nm, specific gravity 10 g / cm3 ) Carbon black particles: Cabot carbon black particles (average particle size 50 nm, specific gravity 1.9 g / cm 3 ) Carbon-coated Ag particles: Carbon-coated Ag particles manufactured by Nisshin Engineering Co., Ltd. (average thickness of the surface carbon coating layer: 1 nm, average particle diameter: 40 nm, specific gravity: 9.5 g / cm 3 ) [Alkali-soluble resin (C)] Carboxyl group-containing epoxy acrylate ZCR-1797H: manufactured by Nippon Kayaku Co., Ltd., propylene glycol monomethyl ether acetate (PGMEA) solution with a solid content of 65% by mass, acid value of 100 mgKOH / g, Urethane-bonded carboxyl group-containing epoxy acrylate UXE-3002: Nippon Kayaku Co., Ltd., PGMEA solution with 65% solids, acid value 100 mgKOH / g [Photopolymerization initiator (D-1)] "Irgacure (registered trademark)" OXE04: manufactured by BASF [Compounds having unsaturated double bonds (D-2)] "Aronix (registered trademark)" M-315: Trifunctional monomer manufactured by Toagosei Co., Ltd. "KAYARAD (registered trademark)" UX-3204: Manufactured by Nippon Kayaku Co., Ltd., a bifunctional monomer containing a urethane bond [Photoacid generator (D-3)] (Synthesis Example 1) Under a dry nitrogen stream, 21.22 g (0.05 mol) of TrisP-PA (trade name, manufactured by Honshu Chemical Industry Co., Ltd.) and 33.58 g (0.125 mol) of 5-naphthoquinone diazide sulfonyl chloride were dissolved in 450 g of 1,4-dioxane and brought to room temperature. 15.18 g of triethylamine mixed with 50 g of 1,4-dioxane was added dropwise so that the temperature in the system did not exceed 35°C. After the dropwise addition, the mixture was stirred at 30°C for 2 hours. The triethylamine salt was filtered, and the filtrate was poured into water. The precipitate was then collected by filtration. The precipitate was dried in a vacuum dryer to obtain a quinone diazide compound. [Epoxy resin (E)] EOCN-102S: Nippon Kayaku Co., Ltd., softening point 65°C, ICI viscosity at 150°C 0.15 Pa s N-680: Manufactured by DIC Corporation, softening point 85°C, ICI viscosity at 150°C 1.1 Pa·s.
[0070] (Synthesis Example 2: Carbon black particle dispersion) 12.0 g of carbon black particles, 3 g of dispersant "DISPERBYK (registered trademark)"-21116 (manufactured by BYK-Chemie), and 85 g of PGMEA were mixed and mixed using a homogenizer at 1,200 rpm for 30 minutes. Thereafter, the mixture was further dispersed using a high-pressure wet media-less atomizer "Nanomizer (registered trademark)" (Nanomizer Co., Ltd.) to obtain carbon black particle dispersion B-1 having an average particle size of 0.15 μm and a conductive particle content of 12.0 wt %.
[0071] (Synthesis example 3: Ag particle dispersion) 65g of Ag particles, 3g of dispersant "DISPERBYK"-21116 (manufactured by BYK-Chemie), and 85g of PGMEA were mixed and mixed for 30 minutes at 1,200 rpm using a homogenizer. After that, the mixture was further dispersed using a high-pressure wet media-less atomizer "Nanomizer" (Nanomizer Co., Ltd.) to obtain an Ag particle dispersion with an average particle size of 0.6 μm and a conductive particle content of 42.5 wt%.
[0072] (Synthesis Example 4: Carbon-coated Ag particle dispersion) 65g of carbon-coated Ag particles, 3g of dispersant "DISPERBYK"-21116 (manufactured by BYK-Chemie), and 85g of PGMEA were mixed and mixed for 30 minutes at 1,200 rpm using a homogenizer.The mixture was then dispersed using a high-pressure wet media-less atomizer "Nanomizer" (Nanomizer Co., Ltd.) to obtain a carbon-coated Ag particle dispersion with an average particle size of 0.2 μm and a conductive particle content of 42.5 wt%.
[0073] Example 1 Into a 100 mL clean bottle were placed 3.58 g of UXE-3002, 0.51 g of "Irgacure" OXE04, 0.10 g of FDG-002, 2.04 g of UX-3204, 2.04 g of EOCN-102S, and 14.45 g of PGMEA, and mixed using a rotation-revolution vacuum mixer "Awatori Rentaro (registered trademark)" ARE-310 (manufactured by Thinky Corporation) to obtain 23.98 g of a resin solution (solid content 34.5 mass %).
[0074] To the resulting 23.98 g of resin solution, 26.83 g of the carbon black particle dispersion obtained in Synthesis Example 2 was added, and mixed again using the rotation-revolution vacuum mixer "Awatori Rentaro" ARE-310 to obtain 50.8 g of photosensitive conductive paste. The resulting photosensitive conductive paste was evaluated for exposure sensitivity and OD value of the dried film by the above-mentioned methods.
[0075] The photosensitive conductive paste obtained was applied onto a soda glass substrate using a spin coater and dried in an oven at 100°C for 10 minutes to obtain a dried film with a thickness of 2 μm. A conductive pattern was formed by exposing the substrate to the minimum light exposure through a negative mask corresponding to the pattern described below and developing with an alkali. Each conductive pattern had a dimension of φ10 μm, and 10 patterns were produced vertically and horizontally within a 3 mm square area, for a total of 100 patterns. The contact area with the substrate per conductive pattern was 78 μm. 2 It was.
[0076] Next, the substrate on which the conductive pattern was formed and the glass substrate to which the transfer was to be made, which had cross marks previously placed at desired positions, were placed face to face with a distance of 50 μm between the substrates, and the substrates were aligned so that the intersections of the cross marks on the glass substrate to be transferred and the center of the conductive pattern overlapped, and a laser was irradiated from the back side of the substrate on which the conductive pattern was formed. The laser had a wavelength of 532 nm, a beam size 1.5 times the conductive pattern, and an energy amount of 100 mJ / cm. 2 , 300mJ / cm 2The conductive pattern was transferred to the receiving glass substrate to obtain a glass substrate with a conductive pattern. The obtained glass substrate with a conductive pattern was used to evaluate the transfer accuracy by the above-mentioned method.
[0077] Similarly, ten conductive patterns with a diameter of 100 μm were formed in a row at intervals of 100 μm within a 3 mm square area on a soda glass substrate, and then the conductive patterns were transferred onto the Au electrodes of a printed wiring board, which was another transfer substrate, by laser irradiation. The laser had a wavelength of 532 nm, a beam size 1.2 times the conductive pattern, and was irradiated with an energy amount of 300 mJ. As a result, a structure with a conductive pattern having a conductive pattern 1 on an electrode 6 of a printed wiring board 5, as shown in FIG. 2, was obtained. The obtained structure with a conductive pattern was used to evaluate the die shear strength, connectivity, and connection reliability by the above-mentioned method.
[0078] (Examples 2 to 13) Except for changing the composition of the photosensitive conductive paste as shown in Table 1, a photosensitive conductive paste, a substrate with a conductive pattern, and a structure with a conductive pattern were prepared in the same manner as in Example 1, and evaluated in the same manner as in Example 1. The evaluation results are shown in Table 2.
[0079] (Examples 14 to 15) Except for changing the electrodes of the printed wiring board to which the conductive pattern was transferred to indium tin oxide, a photosensitive conductive paste, a substrate with a conductive pattern, and a structure with a conductive pattern were prepared in the same manner as in Examples 1 and 12, respectively, and evaluated in the same manner as in Example 1. The evaluation results are shown in Table 2.
[0080] (Examples 16 to 18) A photosensitive conductive paste, a substrate with a conductive pattern, and a structure with a conductive pattern were prepared in the same manner as in Example 1, except that the thickness of the conductive pattern to be formed, the contact area with the substrate, and the aspect ratio were changed as shown in Table 1, and evaluations were performed in the same manner as in Example 1. The evaluation results are shown in Table 2.
[0081] (Example 19) Except for changing the composition of the photosensitive conductive paste as shown in Table 1 and using a positive mask for exposure, the photosensitive conductive paste, substrate with a conductive pattern, and structure with a conductive pattern were prepared in the same manner as in Example 1 and evaluated in the same manner as in Example 1. The evaluation results are shown in Table 2.
[0082] (Comparative Examples 1 to 2) Except for changing the composition of the photosensitive conductive paste as shown in Table 1, a photosensitive conductive paste, a substrate with a conductive pattern, and a structure with a conductive pattern were prepared in the same manner as in Example 1, and evaluated in the same manner as in Example 1. The evaluation results are shown in Table 2.
[0083] [Table 1]
[0084] [Table 2] [Explanation of symbols]
[0085] 1: Conductive pattern 2: Soda glass substrate 3: Laser 4: Transferred substrate 5: Printed wiring board 6: Electrode 7: Silicon chip 8: Electrode 9:Au wiring
Claims
1. A photosensitive conductive paste containing (A) a dye and / or pigment having a maximum absorption wavelength in the range of 500 to 600 nm, conductive particles (B), an alkali-soluble resin (C) and a photosensitizer (D).
2. 2. The photosensitive conductive paste according to claim 1, further comprising an epoxy resin (E) having a softening point of 40° C. or higher and an ICI viscosity at 150° C. of 10 Pa·s or lower.
3. 3. The photosensitive conductive paste according to claim 1, which when applied onto a substrate and heated at 100° C. for 10 minutes gives a dry film having a thickness of 2 μm, the OD value (λ=532 nm) of which is 0.5 or more.
4. 3. The photosensitive conductive paste according to claim 1, wherein the content of the conductive particles (B) is 10 to 30% by volume based on the solid content.
5. 3. The photosensitive conductive paste according to claim 1, wherein the alkali-soluble resin (C) has a urethane bond.
6. 3. The photosensitive conductive paste according to claim 1, wherein the photosensitizer (D) comprises a photopolymerization initiator (D-1) and a compound having an unsaturated double bond (D-2).
7. 7. The photosensitive conductive paste according to claim 6, wherein the compound (D-2) having an unsaturated double bond has a urethane bond.
8. 3. A substrate having a conductive pattern, the substrate having a transmittance of 50% or more of light having a wavelength of 532 nm, the conductive pattern being made of a photopolymerized product of the photosensitive conductive paste according to claim 1 or 2.
9. 9. The substrate with a conductive pattern according to claim 8, wherein the height of the conductive pattern is 0.5 to 3 μm.
10. 9. A method for producing a substrate with a conductive pattern according to claim 8, comprising the steps of forming a film made of the photosensitive conductive paste according to claim 1 or 2 on a substrate which transmits 50% or more of light with a wavelength of 532 nm, exposing and developing the film to form a conductive pattern (conductive pattern forming step).
11. A method for producing a structure with a conductive pattern, comprising a step of irradiating the substrate with the conductive pattern according to claim 8 with laser light having a wavelength of 500 to 600 nm from a substrate side that transmits light with a wavelength of 532 nm, thereby transferring the conductive pattern to an electrode portion of the substrate with an electrode or an electronic component, or to a wiring break portion of the substrate with an electrode or an electronic component (conductive pattern transfer step).
Citation Information
Patent Citations
Method for manufacturing substrate with conductive pattern and method for manufacturing LED mounting circuit board
JP2022055760A
Method for manufacturing display device
WO2022202934A1